Pemanfaatan Media Website “Mantes” untuk Meningkatkan Pengetahuan Masyarakat tentang Cek Kesehatan - Sekar Okta Deliana; Achmad Lukman Hakim; Emi Oktavia Sari; Hikmah Apriyanti; Syifa Pauziah (Sagamedia Indo Press, 2023)
Introduction: Currently Indonesia ranks seventh out of ten countries with the highest prevalence of diabetes mellitus at 10.6% of the total population. Depok City is the area with the highest DM incidence rate in West Java, namely 2.9% of the population. Objectives: This Field Study Practice III aims to educate the importance of health checks, especially for people who have a hereditary history of diabetes mellitus by using the website